Asymptotics of the Solution of Bisingular Problem for a System of Linear Parabolic Equations. I - M. V. Butuzova (Моделирование и анализ информационных систем)
Given a bisingular parabolic problem for a system of linear parabolic equations, we construct an asymptotics for the solution of any order with respect to a small parameter, without using the joining procedure for asymptotic expansions.